2016
DOI: 10.1007/s10334-016-0583-y
|View full text |Cite
|
Sign up to set email alerts
|

3D single point imaging with compressed sensing provides high temporal resolution R 2* mapping for in vivo preclinical applications

Abstract: Accelerated TurboSPI enables preclinical R * mapping without loss of data quality, and may show increased specificity to iron oxide compared to other sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
0
14
1
Order By: Relevance
“…Quantitative information can also be obtained by using a pulse sequence such as TurboSPI . Originally designed for imaging water in porous media that have long normalR2* values but short R 2 values, Rioux et al demonstrated that TurboSPI could also be applied to SPIO‐labeled cells, which exhibited similar magnetic properties .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative information can also be obtained by using a pulse sequence such as TurboSPI . Originally designed for imaging water in porous media that have long normalR2* values but short R 2 values, Rioux et al demonstrated that TurboSPI could also be applied to SPIO‐labeled cells, which exhibited similar magnetic properties .…”
Section: Discussionmentioning
confidence: 99%
“…Originally designed for imaging water in porous media that have long normalR2* values but short R 2 values, Rioux et al demonstrated that TurboSPI could also be applied to SPIO‐labeled cells, which exhibited similar magnetic properties . Although TurboSPI traditionally requires long data acquisition times, the sequence was greatly accelerated for in vivo use by adding compressed sensing reconstruction . It is possible to extract normalR2* maps from TurboSPI, which when combined with in vitro iron‐loading data allows generation of cellular density maps.…”
Section: Discussionmentioning
confidence: 99%
“…Relaxation rate mapping is a popular method for attempting to quantify SPIO labeled cells, since R2* (R2* = 1/T2*) increases linearly as a function of cell density 14,15 . However, many R2* mapping techniques proposed to date are unable to resolve rapidly decaying signals restricting quantitative dynamic range, and prone to blooming artifacts induced by the very species which they are intended to quantify 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous preclinical work done by our lab demonstrated the use of 3D TurboSPI, adapted for quantifying labeled cells 16,17 . TurboSPI is an accelerated multiecho single point imaging (SPI) sequence that was first developed for porous media with short T2* relaxation times (~1ms).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation